CORRELATION OF ANGIOGRAPHIC SEVERITY OF CORONARY ARTERY DISEASE WITH GLYCOCYLATED HEMOGLOBIN IN ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION (Journal of Medical & Health Sciences Review, 2025)
Background: Coronary artery disease (CAD) and type 2 diabetes mellitus (T2DM) frequently coexist and significantly impact cardiovascular morbidity and mortality, particularly in low- and middle-income countries. Glycated hemoglobin (HbA1c) is a well-established biomarker for long-term glycemic control and can serve as a predictor of coronary atherosclerotic disease burden. The study aimed to evaluate the correlation between HbA1c levels in blood and the angiographic severity of CAD, as quantified by the SYNTAX score, in T2DM patients presenting with ST-segment elevation myocardial infarction (STEMI).Methods: Total 74 patients aged 30–70 years with confirmed STEMI and T2DM (HbA1c ≥6.5%) recruited at Lady Reading Hospital Peshawar. Patients underwent coronary angiography, and SYNTAX score was calculated to assess CAD severities. Patients were stratified into good (≤8%) and poor (>8%) glycemic control groups based on HbA1c levels. The relationship between HbA1c and the SYNTAX score was analyzed using Spearman’s correlation and chi-square tests.Results: The mean HbA1c was 8.4 ± 0.9%, and the mean SYNTAX score was 25.2 ± 7.9. Statistically significant moderate positive correlation was observed between HbA1c and the SYNTAX score (r = 0.57, p < 0.001). Patients who had poor glycemic control had significantly higher SYNTAX scores (p < 0.001), with a greater proportion presenting with intermediate to high CAD severity.Conclusion: Elevated HbA1c level is significantly associated with more angiographic severity of CAD in diabetic patients with STEMI. HbA1c may serve as a valuable marker for early risk stratification and intervention planning in acute coronary syndromes, especially in populations with high diabetes prevalence.